Avaliação do desempenho acústico de um hotel com paredes em drywall: estudo de caso - Bolçone, Maria Laura (2023)
The accelerated urban growth and the expansion of industry have led to the development of an increasing number of hotels in urban areas. At the same time, establishments face challenges related to excessive noise, and increasing exposure to external noise. With the aim of establishing minimum performance criteria in relation to environmental comfort, ABNT NBR 15575 addresses issues such as acoustic insulation in relation to internal and external walls and building floors. Thus, this study aims to analyze the acoustic insulation in a hotel in the city of Guarapuava, Paraná. An analysis of the internal insulation system between walls and the insulation system between two independent units located on top of each other was carried out. The focus of the research is air noise, so we analyzed the vertical sealing system of drywall walls and the horizontal sealing system between two apartments, separated by concrete sheet. A detailed study was followed to evaluate the acoustic quality of the environments of interest, following the established normative criteria. Data related to noise pressure levels were collected, considering internal sources at different positions, to determine the magnitude of ambient noise present in each environment analyzed. In addition, the reverb times in each room were also recorded, evaluating the sound absorption capacity and controlled sound. Using R- code programming, the energy average was shown to represent the average sound energy present in each environment. This analysis allowed a more detailed view of the distribution and intensity of sound. The acoustic insulation index was then determined, considering the data collected. After the analysis of the data obtained, it was ensured that all examined rooms meet the minimum criteria required by the applicable standard for both isolation systems analyzed.